(3JYde GddZGJ aj GdUajf GdKGdK hGdSGOS ef eQMdI GdJYdje GdCSGSj hefGgL GdJYdje GdLOjOI (B: (3YqjfI eNJGQI ef bVGA GdRgQGfj, dHfGfs - (3fUQGddg, CMeO QVhGfs ((3HjQhJs (3LGeYI GdbOjS jhSas, 2006)
(3JgOa gPg GdOQGSI Edi bjGS eSJhi JMUjd JdGejP GdUajf GdKGdK hGdSGOS ef eQMdI GdJYdje GdCSGSj aj GddZJjf GdCLfHjI hGdYQHjI aj efWbI ef dHfGf (B((3bVGA GdRgQGfj(B) (3hGdcTa Yf LhGfH GdNdd aj gPG GdJMUjd hJMOjO GdYhGed PGJ GdJCKjQ aj gPG GdeLGd hPdc ef NdGd ebGQHJjf GdChdi fXQjI hGdKGfjI ejOGfjI(B. (3Ef JMbjb eG SHb jJWdH GJHGY GdefgL GdhUaj GdJMdjdj(B. (3CeG ajeG jNU GdYjfI, abO Je GNJjGQgG hab GdWQjbI GdWHbjI GdYThGFjI, hPdc Ydi GdfMh GdJGdj(B: (3YjfI ef GdeOGQS; eOGQS JVe eQMdI GdQhVI hGdGHJOGFj, heOGQS JVe eQMdI GdGHJOGFj hGdeJhSW heG ahb(B. (3YjfI ef GdJdGejP(B: (3JfGhdJ GdOQGSI (B982 (3JdejPkG ef GdbWGYGJ(B: (3GdQSej, GdNGU GdeLGfj, hZjQ GdeLGfj, ef JdGePI GdUajf GdKGdK hGdSGOS GdCSGSj(B. (3YjfI GdeYdejf(B: (3JTed LejY eOQSj GddZGJ ddJdGePI YjfI GdOQGSI(B. (3YjfI GdeOjQjf(B: (3LejY eOjQj eOGQS GdJdGePI GdeTehdjf HGdYjfI, cPdc YjfI GdCgGdj; aJTed ChdjGA CehQ GdWdGH GdeYfjjf HGdYjfI(B. (3oWHb Ydi GdYjfI GdePchQI CYdGg YOO ef GdCOhGJ dLeY GdeYdheGJ GddGReI efgG(B: 1) (3ESJeGQGJ, (B2) (3GENJHGQGJ(B. (3aj BNQ GdOQGSI; Je GdJhUd Edi eG jdj(B: 1) (3HQRJ CYdi eSJhjGJ GdJMUjd GdYdej ajeG jNU GddZGJ, ddZI GdYQHjI ebGQfI eY GdaQfSjI hGdEfLdjRjI, HGdfXQ dfhY GdeOQSI acGf dUGdM GdbWGY GdNGU ebGHd GdQSej(B. 2) (3YfO QHW fJGFL GdGNJHGQ HGdfJGFL GdJQHhjI, HQRJ GdeSJhjGJ GdYGdjI ddeYdejf GdNGVYjf dYOO CcHQ ef GdOhQGJ GddZhjI eY NHQI cHjQI, cPdc eY GdeOjQjf dcf GdfJGFL LGAJ CaVd eY GdEfGK EPG JWQbfG Edi eJZjQ GdLfS aj ehVhY GdEOGQI(B. 3) (3CeG ajeG jNU GdYhGed GdCSQjI, aHQRJ JCKjQGJ hGVMI, LGAJ GdfJGFL dUGdM GdYGFdGJ GdUZjQI hGdhdO cHjQ HGdebGQfI eY GdYGFdGJ GdcHjQI hGdhdO GdeJhSW hGdUZjQ aj GdYGFdI, ceG Cf dGQJaGY eSJhi GdCgd GdJYdjej JCKjQoG EjLGHjkG Ydi eSJhi GdJMUjd GdYdej(B.s
(3GdfhY (B: (3CWQhMIs
Keywords: Cycle primaire Enseignement des langues Curriculum; Elementary Education Teaching languages Curricula; Zahrani; Zahrani; (3GdRgQGfjs; (3GdeQMdI GdGHJOGFjI JYdje GddZGJ GdefGgLs